Strength and conditioning coaches` application of the session rating of perceived exertion method of monitoring within professional Rugby Union - Comyns, T.; Hannon, A. (Journal of Human Kinetics, 2018)
Session rating of perceived exertion (session-RPE) is a method of monitoring and managing training loads. The purpose of this study was to research how and for what purpose strength and conditioning (S&C) coaches implement this monitoring method within professional rugby union. The study also aimed to assess if S&C coaches found this monitoring method to be valid and effective. An online survey containing 24 fixed response questions was used to assess how S&C coaches applied the session-RPE method. The survey was piloted with expert researchers and practitioners in the area of session-RPE prior to distribution and alterations were made to the survey based on the experts` feedback. Twenty S&C coaches working with professional rugby union clubs in Ireland, England, Scotland and Wales completed the survey. The coaches` responses indicated that the majority found the session-RPE to be a valid and effective monitoring method. While some good implementation practices were identified, not all of the coaches adhered to these guidelines which may impact on the accuracy of the collected data. For example, 30% of coaches do not collect the RPE for every session that a player does per week limiting the use of the session-RPE variables cumulative training load, training monotony, training strain and acute:chronic load ratio. S&C coaches within rugby should consider using session-RPE as a method of monitoring and implement the method in a manner reflective of research findings to enhance the potential applications of this system in maximising adaptations and minimising the risk of injury.